Immunosensor-based detection of tungro disease in rice plant - Uda, Muhammad Nur Aiman (2015)
Rice tungro disease is the major constraint, caused by a combination of rice tungro spherical virus (RTSV) and rice tungro bacilliform virus (RTBV). Major outbreaks of tungro have been occurred in countries of South and Southeast Asia, mediated by a viral carrier green leafhopper. To prevent serious outbreaks, detection of Tungro disease requires a fast, simple and sensitive method. The current study was initiated by transferring viruses from the green leafhopper to susceptible plant host varieties (Y1286 and MR81 for RTSV and RTBV, respectively). After inoculation process, both viruses were purified and spectrophotometrically measured as 1.363 and 1.6075 mg mL-1 for RTBV,1.227 and 1.6075 mg mL-1 for RTSV. Viral particles were observed by transmission electron microscopy, where RTBV was observed as 168 mm in length with a bacilliform, whereas RTSV appeared with 35 mm in diameter,showed rod-shaped rounded ends. Next, pure viruses were immunized in White New Zealand rabbits and antibody was analyzed on enzyme-linked immunoassay (ELISA) surface. Analysis with RTBV showed that the second bleed has the highest titer, whereas for RTSV bleed 1 has the highest titer (1.6960 mg mL-1 and 2.3251 mg mL-1). Analysis on screen-printed carbon electrode (SPCE) was incorporated with 0.075 M pyrolle monomer where electro-polymerization process occurred at 0.9 V amperometrically for 20 min. Chronoamperometry measurements showed the best potential to be used is located at 0.2 V, for both RTBV and RTSV. In addition, the antibody immobilized surfaces of SPCE were analyzed by scanning electron microscope. A linear standard curve for each virus obtained based on current measurement (μA), where R2 values were 0.9755 and 0.967, indicates a higher sensitivity of immunosensor developed. Cross reactivity studies, showed the specificity of the antibodies with a low cross-reactivity, although RTBV and RTSV it-self manifested strongest serological cross-reactivity.